Effectiveness of the SAVI (Somatic, Auditory, Visualization, and Intellectual) Learning Model on Students' Science Literacy Ability in Elementary School - Fiteriani, Ida; Baharudin; Uswatun Khasanah; Ida Fiteriani, Ida Fiteriani (JIP Jurnal Ilmiah PGMI, 2024)
This study aims to examine the effectiveness of the SAVI learning model on students' science literacy skill in science subject. The research approach used in this study is quantitative with a quasi-experimental design. The research sample will be purposively selected from two existing ones classes, with one class as the experimental group and one class as the control group. Class B, as the experimental group, will consist of 29 students, while Class C, as the control group, will consist of 27 students, making the total research sample 56 students. In this study, the instrument usedis a test. This test consists of 20 multiple-choice questions designed to measure students' scientific literacy skills after the implementation of the SAVI model. The post-test data will be analyzed using the paired sample t-test statistical method to determine significant differences in scientific literacy skills. The results of this study conclude that the Sig. (2-tailed) value is 0.000 < 0.05. This indicates the effectiveness of the SAVI learning model on the scientific literacyskills of fourth grade students at SDN Purwodadi Simpang. The results of this study are expected to provide practical results guidance for teachers in designing and implementing more effective learning strategies in the classroom. By understanding the impact of the SAVI model on scientific literacy, educators can adapt this method to meet diverselearning needs and improve students' academic outcomes.